Relevansi Pemikiran Ekonomi Islam Al-Maqrizi di Indonesia - isnaini, nur (Jurnal Ilmiah Ekonomi Islam, 2024)
Economic problems always attract people's attention in various fields of life, because economic stability is the basis of people's material well-being. While the monetary phenomenon that causes inflation is a continuous process of currency depreciation. The focus of this research is on the relevance of Al-Maqrizi's Islamic economic thinking in Indonesia, as well as the role of the government in overcoming inflation in Indonesia. The purpose of this research is to find a solution to the problem and control inflation so that it is not high in Indonesia, and to see how the government's policy is in overcoming Indonesian inflation from the perspective of Al-Maqrizi. The method used in this research is descriptive qualitative method. The results of this study are Al-Maqrizi's thoughts which are still relevant to the economy in Indonesia, namely regarding the problems of money and inflation. Al-Maqrizi to overcome the problem of inflation with the establishment of the Baitul Maal. Meanwhile, what the Indonesian government has done in dealing with inflation is combining central bank policies with finance department policies such as a tight money policy by the central bank.